Estimation of above and belowground biomass for grass, herb, and fern species in Peninsular Malaysia - Kenzo, Tanaka; Yoneda, Reiji; Alias, Mohamad Azani (Springer, 2022)
There are no models for estimating the above- and belowground biomass (AGB and BGB) of herbaceous and fern species in Southeast Asia, and therefore we developed a set of allometric equations for this purpose that were applicable to Malaysia. Grass species, herbs, and ferns of different sizes were harvested and excavated to measure the AGB and BGB. After being harvested and oven-dried, the biomass of plant parts was weighed to develop allometric equations between plant size parameters (height and diameter) and biomass. When comparing the allometric equations among the three plant groups (grass, herbs, and ferns), no differences were found between grass and fern groups in both AGB and BGB, whereas herbs versus grass and/or ferns significantly differed. This suggests that the accuracy of the estimation may improve if plant species were separated into these groups. The allometric equation, which pooled all groups, also showed significant relation with high correlation coefficient, and thus it was possible to make estimations with a certain degree of accuracy, even without grouping. The ratio of BGB to AGB (RSR) increased with plant size for herbs and ferns, whereas the RSR was constant with plant size for grasses. These relationships indicated that the RSR potentially used to estimate BGB from AGB with size parameter in each group, though there was larger variation compared with allometric equations. We concluded that developed allometric equations and the RSR can be used to estimate the AGB and/or BGB without the destructive sampling of grassland species in the region.